Mechanisms Predisposing Penile Fracture and Long-Term Outcomes on Erectile and Voiding Functions - Leonardo O. Reis; Marcelo Cartapatti; Rafael Marmiroli; Eduardo Jeronimo de Oliveira Júnior; Ricardo Destro Saade; Adriano Fregonesi (Advances in Urology)
Purpose. To determine the mechanisms predisposing penile fracture as well as the rate of long-term penile deformity and erectile and voiding functions. Methods. All fractures were repaired on an emergency basis via subcoronal incision and absorbable suture with simultaneous repair of eventual urethral lesion. Patients’ status before fracture and voiding and erectile functions at long term were assessed by periodic follow-up and phone call. Detailed history included cause, symptoms, and single-question self-report of erectile and voiding functions. Results. Among the 44 suspicious cases, 42 (95.4%) were confirmed, mean age was 34.5 years (range: 18–60), mean follow-up 59.3 months (range 9–155). Half presented the classical triad of audible crack, detumescence, and pain. Heterosexual intercourse was the most common cause (28 patients, 66.7%), followed by penile manipulation (6 patients, 14.3%), and homosexual intercourse (4 patients, 9.5%). “Woman on top” was the most common heterosexual position (n=14, 50%), followed by “doggy style” (n=8, 28.6%). Four patients (9.5%) maintained the cause unclear. Six (14.3%) patients had urethral injury and two (4.8%) had erectile dysfunction, treated by penile prosthesis and PDE-5i. No patient showed urethral fistula, voiding deterioration, penile nodule/curve or pain. Conclusions. “Woman on top” was the potentially riskiest sexual position (50%). Immediate surgical treatment warrants long-term very low morbidity.